Antecedents of Repurchase Intention: The Case of Private Label Brands in Kerala - A. P., George; Govindan, Yamuna (Indian Journal of Marketing, 2015)
This paper examined the effect of brand loyalty, customer satisfaction, brand trust, customer involvement, perceived value, and brand commitment on consumers’ intention to repurchase private label brands in Kerala. The results indicated that the combined effect of the stated variables on repurchase intention was statistically significant, but the individual effect of each variable on repurchase intention varied significantly. Perceived value appeared to be the most important predictor of repurchase intention followed by commitment. Brand loyalty, brand trust, and customer satisfaction showed negative but statistically significant correlation. Customer involvement did not show statistical significance, though the correlation value was positive. The result indicated that the retail operators should urgently revamp their marketing efforts to build loyalty, customer involvement, trust, and satisfaction to strategically position their private label brands above competitors to achieve market competitiveness and sustainable advantage.